2021
DOI: 10.2147/nss.s310351
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Exosomes and Exosomal MicroRNAs in Postoperative Sleep Disturbance

Abstract: Postoperative sleep disturbance (PSD) often occurs in elderly patients after major surgery and exerts harmful effects on postoperative recovery. PSD may increase the incidence of postoperative fatigue, severe anxiety and depression, pain sensitivity, and cognitive dysfunction, which can cause or aggravate neurodegenerative diseases via amyloid aggregation and tau accumulation. Exosomes are important carriers that mediate the transfer of active substances and genetic information among cells. Recent evidence has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 120 publications
(137 reference statements)
0
5
0
Order By: Relevance
“…[ 27 29 ] Besides, recent research has shown that changes in miRNA expression exert a certain effect on the biological mechanism of POCD. [ 30 , 31 ] More importantly, we show that LncRNA GAS5 suppressed miR-137 in vitro model. Gao et al reported that GAS5 is up-regulated in knee osteoarthritis, and can induce chondrocyte apoptosis through down-regulating miR-137.…”
Section: Discussionmentioning
confidence: 67%
“…[ 27 29 ] Besides, recent research has shown that changes in miRNA expression exert a certain effect on the biological mechanism of POCD. [ 30 , 31 ] More importantly, we show that LncRNA GAS5 suppressed miR-137 in vitro model. Gao et al reported that GAS5 is up-regulated in knee osteoarthritis, and can induce chondrocyte apoptosis through down-regulating miR-137.…”
Section: Discussionmentioning
confidence: 67%
“…There is growing evidence that exosomes may also have a positive impact on neurodegenerative diseases, although some studies showed that exosomes are harmful and may to neurodegenerative diseases [ 47 , 48 ]. We found that miR-184 ASO could rescue the damaged of motor performance and neuronal apoptosis in PD model.…”
Section: Discussionmentioning
confidence: 99%
“…Treatments based on LINGO-1 (LRR and Ig domain containing NOGO receptor interacting protein) antagonism and protein kinase B (Akt) activation in experimental models of cognitive loss in MS may assist to maintain memory function through the promotion of oligodendrocyte differentiation and myelination [145]. Mood disorders that include depression, apathy, and anxiety can accompany the cognitive loss in MS similar to presentations seen in AD [99,[146][147][148][149][150][151]. The cognitive impairment in MS patients also may play a significant role in preventing individuals from returning to prior levels of functioning and the workforce [152].…”
Section: Cognitive Loss and Dementia That Can Occur In Multiple Scler...mentioning
confidence: 99%